PENGGUNAAN LKPD CONCEPT CARTOONS UNTUK MEREMEDIASI MISKONSEPSI PESERTA DIDIK SMP PADA MATERI HUKUM ARCIMEDES - Anoka, Tomi; Sitompul, Stepanus Sahala; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims is to establish the remediation of student?s misconceptions by using LKPD concept cartoons on Archimedes principle at SMP Kristen Immanuel II Sungai Raya. The form of this research is the pre-experimental design which is consisted of one-group of pre-test-post-test design. The sample of this research is students of class VIII D (n = 41 student) which are chosen by random sampling technique of an intact group. This research instrument is a diagnostic test which consists of 9 questions with multiple choices. Based on data analysis, the findings are : (1) The percentage reduction of students who misconceptions, after remediation are 81%, 68%, 64%, and the average is 71%. (2) There is a significant conceptual change whit Mc Nemar statistic test (?_hitung^2 = 44.17; dk = 1 ; ? =0,05) after remediation. The effect size is 1.86 (high category. Based on these results. It was expected that LKPD concept cartoons can be used as an alternative remediation activity to improve misconceptions experienced by the students. Keywords:  Remediation, Misconception, LKPD, Concept Cartoons, Archimedes Principle